Pengaruh Profitabilitas, Keputusan Investasi, dan Likuiditas terhadap Nilai Perusahaan pada Sub Sektor Food & Beverage di BEI (2021–2024) - Agustina, Putri; Setiono, Hari; Ilmiddaviq, Muhammad Bahril (CV. Kalimasada Group, 2025)
Company value is a key parameter used by investors to measure a company's success by looking at its share price, where an increase in share price will have a positive impact on company value and the welfare of its owners. This study aims to determine the influence of profitability, investment decisions, and liquidity on company value in the food & beverage sub-sector on the BEI (2021–2024). This study uses a quantitative method with multiple linear regression analysis techniques. The research sample consists of 21 food & beverage companies selected using purposive sampling techniques. The results indicate that profitability (ROA, ROE) has a positive impact on company value, investment decisions (PER) have a positive impact on company value, and liquidity (CR) does not affect company value. A company's ability to meet its short-term obligations is not always seen as the primary signal in assessing the company's growth prospects. In the context of signaling theory, information about liquidity is considered insufficiently strong to influence investors' perceptions of company value. This means that companies with good liquidity can meet their short-term obligations, thereby enhancing investor confidence and positively impacting company value.